NAVIGATING COMMON GOOD AS THE FRAMEWORK OF PROMOTING RELIGIOUS MODERATION EDUCATION IN INDONESIA - Iqbal, Sopiyan; Kholidi, Muh Azhar; Fitri, Hilwa Alfiani (Universitas Islam Negeri Mataram, 2024)
As a nation with highly multicultural societies, Indonesia comprises various ethnic groups, customs, cultures, and religions. This often triggers societal conflicts between tribes, cultures, and beliefs. For this reason, a model or approach is needed to increase tolerance and respect. Therefore, it is essential to explore the common good values as a framework for promoting religious moderation education through a philosophical approach, particularly in the Indonesian setting. This concept emphasizes the need for cooperation between various beliefs to achieve common goals in creating an inclusive and harmonious society by emphasizing universal moral principles in developing a framework for religious moderation education. Specifically, this study aims to implement the concept of the common good as a universal religious moderation value in Indonesian society as a nation with a significant plurality. The method used in this research is qualitative library research using secondary data. Based on the relevant literature, the results showed that the concept of the common good as the idea of promoting religious education moderation as a solution to the problems of diversity and plurality of religions, cultures, tribes, ethnicities, and groups in Indonesia as a nation with a high level of diversity. This review implies that Indonesian societies ought to embrace the idea of the common good to create harmonious and more tolerant societies in Indonesia.